Performance assessment of routing protocols for campus area emergency delay-tolerant network - Roy, Sujan Chandra; Rahim, Muhammad Sajjadur; Islam, Md Ashraful (International Journal of Advances in Applied Sciences, 2024)
Handheld devices have recently become an indispensable part of our daily lives. These devices always require an end-to-end connection for proper message transmission. Message transmission will be halted if the connection fails. In this case, delay-tolerant networks (DTNs) are preferable. One of the most important applications of DTN is the transmission of emergency messages among rescue personnel in the aftermath of a disaster. Previously, we created a simulation map in the Rajshahi University (RU) campus area of Bangladesh and studied the performance of DTN routing protocols. This paper used our developed simulation map to evaluate the performance of DTN and social-based routing protocols for emergency message circulation in the RU campus area when traditional communication networks are unavailable. We conducted extensive experiments with the opportunistic network environment (ONE) simulator for evaluations. The performance analysis is based on the delivery ratio, average latency, transmission cost, and average hop count of each group when the message size and node density are changed. According to the simulation results, dLife outperforms all other routing protocols in terms of delivery ratio, while the Spray-and-Focus routing protocol outperforms all other performance metrics.